“Confronting the Dragons at the Door”: A Call for Transformative Learning in Teacher Education - Dhakal, Rebat Kumar (Journal of Education and Research, 2017)
This paper examines the beliefs of Nepali teacher educators about the potential of transformative learning (TL) experiences in teacher education. It further explores the ways in which they are promoting TL among the graduate students aspiring to become teacher educators and among the in-service teachers in Nepal. Data collection consisted of qualitative methods, particularly narrative interviewing and observation. Key participants included three emerging transformative education practitioners (teacher educators) and a transformative education pedagogue from Kathmandu University. The narratives of the participants showed that they were stepping up to promote TL in teacher education programmes in Nepal. Their stories revealed that changing the frame of reference of the conventional teachers and thereby instilling in their mind-set the simple thought of TL was like confronting the dragons. Nonetheless, their engagement in teacher education programmes have exposed how students and educators can co-create TL experiences. Their experiences and also my observation of their training programmes showed that Nepali teachers are in want of TL opportunities. The findings suggest that teacher education should foster Critical Consciousness in teachers so that they can develop the ability in their students to analyse, pose questions, and take action on the diverse social, political, cultural, and economic contexts that influence and shape their lives. Moreover, the community of practice among the emerging transformative education practitioners should grow in focus from critical self-reflection to include an emphasis on promoting a contemplative mode of teaching and learning, which will offer an effective pedagogic model to nurture transformative learning in teacher education.